DILEMA SAINS DAN AGAMA - Martha Mulyani Kurniawan (Alucio Dei, 2020)
The rapid development of science and technology has caused many people who do not have the correct understanding to think that science and religion are very contradictory. But on the other hand for people who accept science and technology consider that it is an extraordinary gift that can make it easier for humans. Thus, there is often a debate between science and technology on religious norms. Along with the times, the progress of science and technology is increasingly growing, and of course the development of this technology must be balanced with the truth of the Word of God that has been believed by the congregation as a provision that science and technology cannot affect his faith even though challenges occur in everyday life. Science and technology in human life are things that can support the continuity and ease of human life in daily life, but it needs to be considered usefulness and benefits obtained so that it does not come out of understanding the truth of God's Word